Effect of Pressure Applied During Bonding on the Bond Strength - Mete Özer; Selim Arıcı; Selçuk Karahan (Galenos Yayinevi, 2005)
To investigate the effect of force level applied during bonding of orthodontic brackets on the bond strength of a chemically-cured resin-modified glass ionomer cement. Forty-five extracted human premolar teeth were divided into 3 groups of 15 each. The labial surfaces were pretreated with an application of 10 per cent polyacrylic acid for 20 seconds and then rinsed with water for 20 seconds and slightly dried with a light flow of air before bonding. Fuji Ortho is a powder and liquid system, in which the powder and liquid were mixed in recommended proportions for 30 seconds and this mixture, was applied to the bracket base. Then the cement loaded brackets were placed to enamel surface under 3 different loading force (A: 100 g, B:200 g and C:400 g) applied via a specially designed bonding jig. The excess adhesive was removed using a scaler and magnifying glass when the samples were under this constant pressure. The tooth/bracket combinations were then left undisturbed for 5 minutes at room temperature before being stored in water at 37°C for 24 hours. The bonded brackets were subjected to tensile test on a Lloyd LRX testing machine. The data was analyzed statistically to determine the significance of differences between experimental groups. Analysis of variance showed significant differences between the mean tensile bond strengths of groups at the 95 % level of confidence (p <0.05). The grouping of these differences by Tukey's HSD multiple-range test indicated that the brackets bonded under 200 grams of force (B) showed significantly higher mean tensile bond strength (10.47 MPa) than that of the brackets bonded under 400grams of force(C). The force level applied during the direct bonding had an important affect on the tensile bond strength of the resin-modified glass ionomer cement.